2024
DOI: 10.2169/internalmedicine.2429-23
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cytokine Release Syndrome and Immune Effector Cell-associated Neurotoxicity Syndrome in a Man Receiving Immune Checkpoint Inhibitors for Lung Cancer

Takaaki Tanaka,
Masataka Taoka,
Go Makimoto
et al.

Abstract: A 55-year-old man with stage IV lung adenocarcinoma was treated with cisplatin, pemetrexed, nivolumab, and ipilimumab. Approximately 100 days after treatment initiation, he became disoriented and presented to the emergency department with a high fever. Blood tests revealed liver and kidney dysfunctions. Subsequently, the patient developed generalized convulsions that required intensive care. He was clinically diagnosed with cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…There was no acute fever, electrolyte disturbance, carcinomatosis, brain metastasis, head trauma, illicit drug dependence, or insomnia that could explain the occurrence of seizures. Second, ICANS has already been reported in association with CD20 blockers [ 2 , 11 ]. Tanaka et al reported the case of a 55-year-old male with lung cancer who was treated with cisplatin, pemetrexed, nivolumab, and ipilimumab and developed ICANS 100 days after starting therapy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was no acute fever, electrolyte disturbance, carcinomatosis, brain metastasis, head trauma, illicit drug dependence, or insomnia that could explain the occurrence of seizures. Second, ICANS has already been reported in association with CD20 blockers [ 2 , 11 ]. Tanaka et al reported the case of a 55-year-old male with lung cancer who was treated with cisplatin, pemetrexed, nivolumab, and ipilimumab and developed ICANS 100 days after starting therapy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, ICANS has already been reported in association with CD20 blockers [ 2 , 11 ]. Tanaka et al reported the case of a 55-year-old male with lung cancer who was treated with cisplatin, pemetrexed, nivolumab, and ipilimumab and developed ICANS 100 days after starting therapy [ 2 ]. The patient suffered from high fever, disorientation, and seizures and responded positively to glucocorticoids and immunosuppression [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokine release syndrome (CRS) is relatively rare in patients treated with ICIs, as evidenced by an incidence of approximately 4.6% reported in a single-center retrospective study ( 19 , 97 , 98 ). However, once it occurs, it tends to be persistently severe and potentially life-threatening ( 99 , 100 ). CRS, as a systemic inflammatory response mediated by inflammatory cytokines, is directly triggered by immunotherapy.…”
Section: Etiology Of Fever Of Unknown Origin Induced By Icismentioning
confidence: 99%